Um olhar bakhtiniano sobre a produção escrita de estudantes do ensino médio : processos argumentativos - França, Domingos Pinto de (2018)
This dissertation aims to reflect on the difficulties of high school students in arguing in their texts, in both cases oral and written. And a propose of work with a focus on writing from the approach of genres in the Bakhtinian perspective. Initially, our proposal was to investigate how the production of texts occurs in a public school in Cuiabá-MT, where the teacher's planning used the argument as a subject that triggered the textual productions during class. The subjects of our research were followed in the first and second years of high school, as well as in specific moments during the learning of the theory of genres with the teachers involved. The theoretical basis of the research is anchored in authors who work specifically with the argumentation as Perelman and Tyteca (2005). We also have contributions from the studies of Fiorin (2016), Pistori (2010), Mosca (2006), Antunes (2003) and Oliveira (2009) among others, seeking answers to the following questions: a) Can students become protagonists, gaining authorship by producing their texts in a pedagogical practice based on argumentative processes based on the Bakhtinian proposals? b) After the learning process, over a year, did the students improve their textual productions using the argument? In the description of the data, we elaborated the answers to these questions. We did the analysis of the texts produced by the students during the period of data collection and we confront the theories presented here in order to investigate them. From the analysis we could note that the results, although not very promising, showed that students improve their textual productions. We also note that a more effective work is needed in the teaching of textual argumentation since the initial grades.